Mentalization based treatment of youth on the psychotic spectrum: clinical profiles and outcomes for youth in the ECID - Dangerfield, Mark; Brotnow Decker, Line (Frontiers in Psychiatry, 2023)
Early intervention may significantly improve the prognosis associated with psychotic disorders in adulthood. The present study examined the acceptability and effectiveness of a standalone intensive, in-home, mentalization-based treatment (MBT) for extremely high-risk, non-help-seeking youth on the psychotic spectrum (Equipo Clínico de Intervención a Domicilio (ECID), Home Intervention Clinical Team). Despite previously being unable to participate in treatment, more than 90% of youth engaged and those on the psychotic spectrum demonstrated slightly higher engagement than the general high-risk group (95% and 85%, respectively, X1=4.218, p=.049). Generalized estimating equation (GEE) models revealed no main group effect on the likelihood of reengaging with school over the first 12 months of treatment (X1=1.015, p=.314) when controlling for the duration of school absenteeism at intake. Overall, the percentage of school engagement rose from 12 to 55 over this period, more than 40% of the total sample experienced clinically reliable change and an additional 50% appeared clinically stable. No statistically significant difference was observed between the groups in the average change in HoNOSCA total severity score (X1=0.249, p=.618) or the distribution of youth into categories of clinical change during the first year of treatment (X1=0.068, p=.795). The present findings suggest that a mentalization based intervention may be able to engage extremely high-risk youth in treatment and have clinically meaningful impact on symptom severity and functioning after 12 months.